Kontribusi Financial Technology Peer-to-Peer Lending dalam Membantu Pembiayaan Petani Guna Meningkatkan Produktivitas Usaha Tani (Studi Kasus pada Petani di Kecamatan Way Panji Kabupaten Lampung Selatan) - Wijaya, Komang David Saputra; Amna, Luke Suciyati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to explore the potential for using financial technology, such as digital platforms and mobile applications, to facilitate access to financing for farmers in rural areas who have limited digital literacy. The problem often faced by farmers is a decrease in harvest yields which causes limited capital in managing their farming business so that farmers' productivity decreases, with minimal harvest results, of course, not only limits their ability to meet their daily living needs but also hinders efforts to collect capital which is crucial for the continuation of production in the next planting season, so they are forced to take out loans from financial institutions. One alternative investment in the capital sector is a source of community income because through investment and a peer-to-peer financing system, borrowers can obtain very good income. The research utilized a qualitative descriptive design using secondary data as the main research data source. The research results show that the implementation of fintech P2P lending has had a significant positive impact in increasing farmer productivity in Way Panji District. Based on the problems of farmers in Way Panji who previously had difficulty accessing financing, this can now make it easier for farmers to obtain funds for business capital. Fast and flexible financing provides opportunities for farmers to purchase higher quality seeds, fertilizer and agricultural equipment, which will ultimately increase farmers' production results.